Konten Prank Youtuber Sebagai Tindak Pidana Berdasarkan Undang-Undang Informasi dan Transaksi Elektronik: Youtuber Prank Content as a Crime Under the Information and Electronic Transactions Law - Yasa, I Wayan Budha; Wiguna, Gede Yudiarta (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
Prank is a form of joke or joke that is intentionally made by someone with the intention of pranking or pranking other people with the aim of creating a sense of satisfaction for the prank maker. There are various types of pranks that are generally made to be later used as personal or group content available on various social media such as YouTube. Prank content created by someone like a YouTuber (YouTube content creator) can be considered a crime, even if a prank is a joke or a joke. This is because someone who is a victim of this prank may be harmed or their rights may be violated. The purpose of this study is to find out and analyze YouTuber prank content which can be categorized as a crime under the Information and Electronic Transactions Act and the regulation of YouTuber prank content which is categorized as a crime in the Electronic Information and Transactions Act. The method used in this research is normative juridical using a legal and conceptual approach. The technique of collecting legal materials used is document study by examining primary and secondary legal materials. The method of analyzing legal materials is carried out in a normative juridical manner which is presented descriptively. Based on the results and discussion of this research, it was found that YouTuber prank content which can be categorized as a criminal offense under the Information and Electronic Transactions Act is prank content that contains content that violates decency, insults and/or defamation, and can cause hatred or hostility of certain individuals and/or community groups based on ethnicity, religion, race, and inter-group (SARA). Then it was found that, the regulation regarding YouTuber prank content which is categorized as a crime in The Information and Electronic Transaction Law is regulated in Article 27 paragraph (1) and (3) junto Article 45 paragraph (1) and (3) and Article 28 paragraph (2) junto Article 45A paragraph (2).